Delayed Diagnosis of Vulvar Crohn's Disease in a Patient with No Gastrointestinal Symptoms - Leah Ellis Wells; David Cohen (Karger Publishers, 2018)
Though Crohn's disease primarily affects the gastrointestinal tract, cutaneous Crohn's disease of the vulva can occur in the absence of gastrointestinal symptoms, complicating the diagnosis. Once clinicians suspect cutaneous Crohn's disease, antibiotics and traditional immunosuppressants comprise initial treatment. Unfortunately, sometimes these therapies are not effective, or they provide only short-lived symptomatic improvement. A few case reports have found tumor necrosis factor-α inhibitors to be helpful in such refractory cases. We describe a patient with long-standing, painful vulvar Crohn's lesions with no gastrointestinal manifestations of the disease. Her diagnosis was delayed for years, and initial therapy with antibiotics and steroids was unsuccessful. Finally, the patient experienced effective and long-lasting symptom improvement with infliximab (RemicadeTM).